Systematic Literature Review: Hasil Kerajinan Tangan Dalam Kajian Etnomatematika - Sisfarina Hafifah; Aan Putra (Elementar : Jurnal Pendidikan Dasar, 2022)
Abstract* This article discusses about improving mathematics learning in ethnomathematical learning through handicrafts. This study aims to conduct an ethnomathematical study of the results of handicrafts and their relation to mathematics learning. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting and reviewing all articles regarding the results of handicrafts. The articles used in this study were 14 accredited national journal articles obtained from the Google Scholar database. Based on this research, it was found that the results of handicrafts in ethnomathematical studies can improve mathematics learning.Keywords: Handicraft Results, Ethnomathematics, Systematic Literature ReviewAbstrak* Artikel ini membahas tentang meningkatkan pembelajaran matematika pada pembelajaran etnomatematika melalui hasil kerajinan tangan. Penelitian ini bertujuan untuk melakukan kajian etnomatematika tentang hasil kerajinan tangan dan kaitannya dengan pembelajaran matematika. Metode penelitian yang dipilih dalam penelitian ini ialah metode SLR (Systematic Literature Review). Pengumpulan data dilakukan dengan mendokumentasi dan mereviu semua artikel mengenai hasil kerajian tangan. Artikel yang digunakan pada penelitian ini sebanyak 14 artikel jurnal nasional terakreditasi yang diperoleh dari database Google Scholar. Berdasarkan penelitian ini didapatkan bahwa hasil kerajinan tangan dalam kajian etnomatematika dapat meningkatkan pembelajaran matematika.Keywords: Hasil Kerajinan Tangan, Etnomatematika, Systematic Literature Review